Qualifications of Petri nets for modeling of logistical systems - Petr Jedlička (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2006)
Simulation and optimization is one of the most popular approaches to improve the use of simulation models as a tool to obtain the best system configuration. Petri nets have proved to be useful for examining the performance of different system configurations and/or alternative operating procedures for various systems. Based on their precise semantics and easy-to-understand graphical representation, Petri nets are appropriate to model logistic systems together with their quantitative and qualitative properties. In this paper, potential benefits of usage of object-oriented Petri nets for optimization of logistical systems are discussed.